2024
DOI: 10.7554/elife.87458
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation of gut microbial metabolite indole-3-acetate alleviates diet-induced steatosis and inflammation in mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in Western countries. There is growing evidence that dysbiosis of the intestinal microbiota and disruption of microbiota-host interactions contribute to the pathology of NAFLD. We previously demonstrated that gut microbiota derived tryptophan metabolite indole-3-acetate (I3A) was decreased in both cecum and liver of high-fat diet-fed mice and attenuated the expression of inflammatory cytokines in macrophages and TNF-a and fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…In our microbiome analysis of GF offspring, we found I3A was positively associated with S24-7 (also known as Muribaculaceae), and negatively associated with both Parabacteroides and unclassified Mogibacteriaceae. Other studies have shown that maternal WD exposure reduces offspring I3A in the liver and cecum and is associated with depleted abundances of Bacteroidetes and Muribaculaceae (S24-7) [82]. Lactobacillus and S24-7 family members are considered beneficial bacteria and are typically associated with a "healthy" microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In our microbiome analysis of GF offspring, we found I3A was positively associated with S24-7 (also known as Muribaculaceae), and negatively associated with both Parabacteroides and unclassified Mogibacteriaceae. Other studies have shown that maternal WD exposure reduces offspring I3A in the liver and cecum and is associated with depleted abundances of Bacteroidetes and Muribaculaceae (S24-7) [82]. Lactobacillus and S24-7 family members are considered beneficial bacteria and are typically associated with a "healthy" microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In our microbiome analysis of GF offspring, we found I3A was positively associated with S24-7 (also known as Muribaculaceae ) and negatively associated with both Parabacteroides and unclassified Mogibacteriaceae . Other studies have shown that maternal WD exposure reduces offspring I3A in the liver and cecum and is associated with depleted abundances of Bacteroidetes and Muribaculaceae ( S24-7 ) [ 77 ]. Lactobacillus and S24-7 family members are considered beneficial bacteria and are typically associated with a “healthy” microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered I3A, a gut microbiota-derived tryptophan metabolite, alleviates liver steatosis and inflammation in a mouse model of diet-induced non-alcoholic fatty liver disease. Notably, I3A does not alter the intestinal microbiome, suggesting that the I3A's beneficial effects likely reflect the metabolite's direct actions on the liver [38]. In colitic mice, the administration of I3C triggers an IL-22-dependent mechanism that attenuates colonic inflammation, and prevents the microbial dysbiosis caused by colitis by increasing a subset of Gram-positive bacteria known to produce butyrate [39].…”
Section: Anti-inflammatory Effects Of Ahr In the Intestinementioning
confidence: 99%